2012
DOI: 10.1590/s0080-62342012000600004
|View full text |Cite
|
Sign up to set email alerts
|

Estomas em neonatologia: um resgate da memória materna

Abstract: RESUmoO panorama da produção científica no que concerne à família e estomas é carente de estudos sobre o tema, em especial sobre a experiência no período neonatal da criança. O presente estudo teve como objetivo geral compreender a experiência da mãe que tem um filho estomizado durante o período neonatal ou durante o tempo de internação em Unidade de Terapia Intensiva Neonatal (UTIN). Utilizando a História Oral como referencial metodológico, foram realizadas entrevistas com nove mães. O resgate das memórias in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…Relationships between nurses and the families of hospitalized children are characterized by a lack of clarity regarding both roles; as a result, the difficulties of negotiation permeate the relationships established. Interpersonal relations between nurses and parents are inadequate, inappropriate and ineffective (2,(7)(8)(9)(10) . At present, no tool is available for the assessment of nurses' self-efficacy for establishing a good relationship with the family.…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between nurses and the families of hospitalized children are characterized by a lack of clarity regarding both roles; as a result, the difficulties of negotiation permeate the relationships established. Interpersonal relations between nurses and parents are inadequate, inappropriate and ineffective (2,(7)(8)(9)(10) . At present, no tool is available for the assessment of nurses' self-efficacy for establishing a good relationship with the family.…”
Section: Introductionmentioning
confidence: 99%
“…O uso de tecnologias leves difere do ambiente de uma unidade de terapia intensiva. 21 Referente à educação em saúde, o enfermeiro deve ser capaz de orientar a família do RN, esclarecendo-lhes sobre: o motivo da realização da estomia; a cirurgia; o que é uma estomia intestinal; quais são os cuidados necessários; como realizar o manejo da estomia; as possíveis complicações. Uma vez que a confecção da estomia no RN é encarada pela família como um risco de morte e/ou de possibilidade de desospitalização do RN, essas orientações objetivam diminuir o medo do desconhecido e promover o engajamento da família diante das alterações físicas do RN.…”
Section: Discussionunclassified
“…Uma vez que a confecção da estomia no RN é encarada pela família como um risco de morte e/ou de possibilidade de desospitalização do RN, essas orientações objetivam diminuir o medo do desconhecido e promover o engajamento da família diante das alterações físicas do RN. 17,21,22 A família que recebe as orientações de forma adequada, diminui as chances de reinternações por complicações com a estomia. 3,22 Portanto, a participação efetiva da equipe de enfermagem na educação em saúde da família pode melhorar a qualidade de vida do RN e de sua família.…”
Section: Discussionunclassified
“…Considering that this process will affect the whole life trajectory of the individual in physiological, psychological, and psychosocial terms, it is considered important to provide an individualized consultation to each child; to plan training at a level that can be understood by the child; to continue consulting also on education, social life, complications, and care during the period after preparation; and to introduce children and adolescents with other individuals having an ostomy to benefit from their experiences. In a qualitative study conducted with mothers of babies with ostomies in the neonatal intensive care unit (Cruz & Angelo, 2012), it was reported that their maternal-infant bonds were affected because mothers saw their children for limited time periods. Furthermore, it was reported that mothers want to spend more time with their children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some parents indicated that they thought their children would experience pain because of ostomy and, thus, they were worried, whereas some other parents declared that they saw the presence of ostomy as a chance of life for their child and they tried to adapt to their new lives. They also emphasized that communication with pediatric surgical clinic nurses was very important and they should be given education on the subjects appropriate for the condition of their babies (Cruz & Angelo, 2012). Nurses are recommended to plan interventions within the framework of family-centered care according to the beliefs, feelings, and needs of children, adolescents, and parents (Leite et al, 2016; Melo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%